Heat‐treated emulsions with cross‐linking bovine serum albumin interfacial films and different dextran surfaces: Effect of paclitaxel delivery. Issue 4 (6th February 2013) - Qi, Jianing; Huang, Chong; He, Fen; Yao, Ping
Abstract In this study, a type of biocompatible and biodegradable oil‐in‐water emulsion for hydrophobic drug delivery was evaluated in vitro and in vivo. Bovine serum albumin (BSA)–dextran conjugates with different dextran molecular weights and different conjugation degrees were used as the emulsifier and stabilizer. Paclitaxel (PTX), a hydrophobic antitumor drug, was effectively loaded inside the oil droplets via high‐pressure homogenization. The emulsions were heated at 90°C for 1 h to eliminate the anaphylaxis of BSA. By virtue of the cross‐linked BSA films at the oil–water interfaces produced by the heat treatment and the hydrophilic dextran surfaces, the emulsions are stable in blood serum, as well as stable against long‐term storage. In vitro cytotoxicity study verifies that the unloaded emulsions are biocompatible and the PTX‐loaded emulsions have similar antitumor activity as PTX solution. In vivo investigation of murine ascites hepatoma H22‐tumor‐bearing mice demonstrates that the PTX‐loaded emulsion with shorter and denser dextran surface has better tumor inhibition and survivability efficacy than the commercial PTX injection. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1307–1317, 2013